Optimizing Transportation Routes and Costs in Crude Palm Oil Supply Chains using Linear Programming: A Case Study of PT.X, OKU Regency, South Sumatera - Pramestari, Diah; Djatna, Taufik (Journal of Computer Science and Engineering (JCSE), 2025)
Transportation is a crucial factor that significantly impacts the supply chain. Because there aren't enough roads and other ways to get around, it's hard for one of the companies in OKU Regency that makes crude palm oil to get its products to customers, especially when it rains. The company that produces cooking oil received a delivery of crude palm oil, accounting for 90% of total production, from PT.X. The delivery of crude palm oil to PT.Y was received later than the original schedule. Number formulas that are meant to solve PT.X transportation problems can be written in terms of linear programming methods. From the stages of collecting, processing data and testing formulations using the LINDO application, it was discovered that under ideal conditions there are 9 alternative transportation routes from origin city B to destination city TJ with the shortest time of 9 hours. The delivery of transportation mode uses 12 tanks with 9.5 tons capacity and 17 tanks with 8 tons capacity and the lowest transportation expenses are Rp. 487.580. The results of the general mathematical formulation can then be used to solve transportation problems for other cases with similar conditions to PT.X. This mathematical formulation can be used for making decisions in selecting transportation routes, selecting modes and transportation costs. Changes in production factors such as capacity, number of orders, travel time, delivery distance, fuel prices, and toll rates can change the decisions made by entering their actual values in the general mathematical formula that has been produced.